(untitled) (Bangladesh Journal of Medical Microbiology, 2026)
Background: Clinical diagnosis can be challenging as dermatophytoses often mimic other dermatoses, underscoring the need for accurate laboratory methods. Objectives: The purpose of the present study was to isolate and identify dermatophyte species using both phenotypic and molecular approaches. Methodology: This cross-sectional study was conducted over one year in the Department of Microbiology, Chittagong Medical College, Chattogram, Bangladesh enrolling 300 patients with clinically suspected dermatophytosis from the Department of Dermatology and Venereology at Chittagong Medical College Hospital, Chattogram, Bangladesh. The clinical samples (skin, hair, and nails) were subjected to direct microscopy and culture on Dermatophyte Test Medium and Sabouraud’s Dextrose Agar. Identification was based oncolony morphology, lactophenol cotton blue staining, and biochemical tests, including urease and hair perforation. Molecular confirmation was done via PCR using pan-dermatophyte and species-specific primers. Results: Out of 300 samples, 103(34.3%) were culture-positive, with microscopy positivity in 31.7% and concordant results in 29.0%. Most cases were in the 21 to 30 age group, with a female predominance (67.0%). Tinea corporis was the most common clinical presentation, and Trichophyton mentagrophytes was the predominant species. PCR confirmed 95.14% of culture-positive isolates; 88 were identified at the species level, while 10 showed no amplification. Conclusion: Traditional methods remain valuable; PCR offers improved accuracy in species identification and supports better management of dermatophytic infections. Bangladesh Journal of Medical Microbiology, July 2025;19 (2):129-135